2018
DOI: 10.3329/jssmc.v9i2.37268
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Stapled Haemorrhoidectomy for Primary Haemorrhoid – Our Experience in ShSMCH

Abstract: [J Shaheed Suhrawardy Med Coll 2017; 9(2): 78-82]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[10] According to Saha et al, in a study conducted in 2017, it was found that hemorrhoidectomy with a stapler had a shorter hospital stay compared to conventional hemorrhoidectomy (the ratio of one-day surgery was 89.2% with conventional techniques compared to 82% with the stapled hemorrhoidopexy technique) and the average the average postoperative patient with stapled hemorhoidopexy takes 8 days to return to normal work activities compared to conventional techniques which take 16 days. [11] In this study, it was found that the average length of stay of patients after stapled hemorhoidopexy was shorter than that of open hemorrhoidectomy, while the longest duration of hospitalization for both open hemorrhoidectomy and stapled hemorhoidopexy was 15 days. The average length of hospitalization for the two procedures is also the same as in some literature which states that the advantage of stapled hemorhoidopexy is the shorter duration of hospitalizations.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 68%
“…[10] According to Saha et al, in a study conducted in 2017, it was found that hemorrhoidectomy with a stapler had a shorter hospital stay compared to conventional hemorrhoidectomy (the ratio of one-day surgery was 89.2% with conventional techniques compared to 82% with the stapled hemorrhoidopexy technique) and the average the average postoperative patient with stapled hemorhoidopexy takes 8 days to return to normal work activities compared to conventional techniques which take 16 days. [11] In this study, it was found that the average length of stay of patients after stapled hemorhoidopexy was shorter than that of open hemorrhoidectomy, while the longest duration of hospitalization for both open hemorrhoidectomy and stapled hemorhoidopexy was 15 days. The average length of hospitalization for the two procedures is also the same as in some literature which states that the advantage of stapled hemorhoidopexy is the shorter duration of hospitalizations.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 68%